Liability insurance in international arbitration : the Bermuda Form - Jacobs, Richard, QC.; Masters, Lorelie S.; Stanley, Paul, 1970- (London, England : Zed Books, 2004)
"Insurance policies written on the Bermuda Form have a distinctly international flavour. The policyholder and the insurers are often based in different countries. The policy includes an express choice of New York law (with certain modifications), and invariably provides for disputes to be settled by arbitration, usually in England, sometimes in Bermuda."--Page [29].
The legal and economic origins of the Bermuda Form -- The Bermuda Form: its basic structure -- Choice-of-law issues under the Bermuda Form -- Interpretation of the Bermuda Form and the modification of New York law -- The coverage clause -- The definition of 'occurrence' -- Fortuity, expected or intended, and the 'maintenance deductible' -- Notice of occurrence -- Article II: The excess point and limits of liability -- The exclusions -- The conditions -- Misrepresentation and non-disclosure -- Waiver and estoppel and reservations of rights -- Commencing a Bermuda Form arbitration and appointing attorneys and arbitrators -- The course and conduct of a Bermuda Form arbitration in London -- Discovery, privilege, and waiver of privilege.
Includes bibliographical references (pages 347-350) and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Liability insurance -- United States; Insurance claims -- United States; Liability insurance -- Great Britain; Insurance claims -- Great Britain; Arbitration and award; International arbitration,Insurance law,Civil procedure, litigation & dispute resolution,Comparative law; Electronic books